Challenges, Opportunities and Options for the Development of Rural Financial Institutions - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2000)
Why does IFAD need rural finance guidelines? With its exclusive emphasis on rural poverty alleviation, IFAD enjoys a competitive advantage over other development agencies, and should strengthen its role by providing support for the development of rural finance as an important instrument. The goal of IFAD?s support for rural finance is the sustainable improvement of the livelihood of the rural poor. This paper offers guiding principles to IFAD?s staff and partner institutions to stimulate innovation and deepen impact by providing options for the effective development of sustainable financial services of increasing outreach to the rural poor. Once adopted, it will serve as a basis for the elaboration of more specific technical papers as well as strategy papers within IFAD?s regional divisions.
Keywords: 330; Ländlicher Finanzmarkt; Entwicklungsländer; International Fund for Agricultural Development